2020
DOI: 10.1039/c9sc04569d
|View full text |Cite
|
Sign up to set email alerts
|

From 1,2-difunctionalisation to cyanide-transfer cascades – Pd-catalysed cyanosulfenylation of internal (oligo)alkynes

Abstract: The intra- and intermolecular Pd-catalysed cyanosulfenylation of internal alkynes enables the formation of tetrasubstituted thioacrylonitriles and is extended to oligoyne systems leading to oligoenes and a cyanide transfer over four or six atoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 59 publications
0
15
0
1
Order By: Relevance
“…[47c] A sulfur-based polycycle synthesis (198) was recently demonstrated via a thiopalladation, double insertion into unsaturation, and a cyanide transfer in a cascade process (10-99 % yields). [48] Cyanoselenylation via a similar pathway was also reported to access selenoenol ethers. [49] Matsude et al [50] recently demonstrated a cascade cyclization of optically active 1,1-diarylmethylcarbonates 199 via Mizoroki-Heck followed by Suzuki coupling to furnish trans-1,2disubstituted indanes 200 (Scheme 30).…”
Section: Electrophilic Activation/reductive Elimination Cà C Bond Formation Via Nucleopalladationmentioning
confidence: 90%
“…[47c] A sulfur-based polycycle synthesis (198) was recently demonstrated via a thiopalladation, double insertion into unsaturation, and a cyanide transfer in a cascade process (10-99 % yields). [48] Cyanoselenylation via a similar pathway was also reported to access selenoenol ethers. [49] Matsude et al [50] recently demonstrated a cascade cyclization of optically active 1,1-diarylmethylcarbonates 199 via Mizoroki-Heck followed by Suzuki coupling to furnish trans-1,2disubstituted indanes 200 (Scheme 30).…”
Section: Electrophilic Activation/reductive Elimination Cà C Bond Formation Via Nucleopalladationmentioning
confidence: 90%
“…Recently, the realm of cyano-functionalization was further explored by Werz and coworkers by palladium catalysis and was utilized for the cyanosulfenylation 56 and cyanoselenylation 57 of internal alkynes independently in 2020 (Scheme 56). Both aromatic and aliphatic thiocyanates underwent the syn-1,2cyanosulfenylation of internal alkynes and could access the tetra-substituted double bonds with sulphur and cyano in adjacent positions.…”
Section: Alkenyl and Alkynyl C-h Cyanationmentioning
confidence: 99%
“…Very recently, Werz and co-workers described the first example of Pd-catalyzed intramolecular cyanosulfenylation of a triple bond and applied this method to the synthesis of two medium-sized heterocycles 47, one oxathiocin and one oxathionin (Scheme 18) [55]. Mechanistically, the sequence consists of a thiopalladation-cyanide transfer cascade.…”
Section: C-s Bond Formationmentioning
confidence: 99%